Pemberdayaan Masyarakat Melalui Program Bank Sampah (Studi pada Kampung Edukasi Sampah di Kelurahan Sekardangan Kecamatan Sidoarjo Kabupaten Sidoarjo) - Amalia Dewi Safitri; Ilmi Usrotin Choiriyah (Universitas Batanghari Jambi, 2023)
The growth that has occurred in Sidoarjo City has caused an increase in population from an environmental perspective, this has had an impact on increasing the volume of waste in Sidoarjo City, so that the Sekardangan Subdistrict TPA definitely has a lot of waste capacity. The Sidoarjo City Government must be proactive in addressing this problem, including empowering the community through waste management in waste banks. This government applied research was carried out in Sekardangan Village, Sidoarjo District, Sidoarjo Regency with the aim of finding ways to empower the community in managing waste at village waste banks, educating, preventing inhibiting factors and efforts to overcome these inhibiting factors. This study used descriptive qualitative method. Data was collected through interviews, observations and notes. Data analysis was carried out by data reduction, data presentation and drawing conclusions. This research aims to examine and understand more deeply the empowerment of the Sekardangan Village community in waste management and the obstacles to community empowerment at the Sekardangan Village TPA, Sidoarjo Regency. The results of this government applied research show that community empowerment in waste management in waste banks is included in a development perspective. Human development, trade and the environment are quite good, but several aspects of institutional development are still lacking. Obstacles faced in empowering the community through the Waste Education Village Waste Bank Program in Sekardangan Village, Sidoarjo District, Sidoarjo Regency. Lack of public understanding of waste classification, low community capacity in waste management, lack of community skills in waste management.